The Interplay between Workload Pressures, Negative Work Environments, and Employee Motivation - Wahyudi, Wahyudi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The dynamics between workload pressures, negative work environments, and employee motivation are crucial in understanding workplace productivity and employee well-being. This study explores how these factors interplay within PT. Fouher Popular Internasional. A quantitative approach was employed using a survey method. Data were collected through a questionnaire distributed to a sample of 83 employees at PT. Fouher Popular Internasional. The findings reveal significant correlations between high workload pressures and decreased motivation, as well as between negative work environments and reduced employee engagement. These interactions highlight the need for effective management strategies to mitigate these issues.